Antipredator responses of ship rats to visual stimuli: combining unimodal predation cues generates risk avoidance. (October 2020) - Farnworth, Bridgette; Innes, John; Davy, Michael; Little, Lauren; Cave, Vanessa; Waas, Joseph R.
Abstract : Using information from multiple predation cues may allow prey to accurately assess predation risk and correlate antipredator responses with the intensity of the threat. We assessed whether combined unimodal cues would enhance antipredator behaviour in captivity by presenting 10 wild-caught ship rats, Rattus rattus, with direct and indirect simulated visual predation cues, either alone or in combination. We measured changes in activity and foraging behaviours to examine how antipredator behaviour differed when rats were exposed to bright light (an indirect visual predation cue), a looming stimulus (a direct visual predation cue that simulates an attacking aerial predator) and bright light combined with the looming stimulus (direct and indirect visual cues combined). In most cases, the combined visual cues significantly enhanced antipredator responses relative to control conditions (i.e. no looming stimulus and low light); rats adopted cautious foraging strategies and exhibited sustained avoidance behaviour. Ship rats appear to amplify their responses to risk when exposed to combined unimodal predation cues; the finding could be exploited to control the activities of rodent pests, but also warns of possible impacts of multiple sensory pollutants. Highlights: Amalgamating information from two unimodal predation cues can inform prey behaviour. Direct and indirect predation cues may interact to amplify defensive behaviour. Presenting combinations of predation cues may enhance pest management strategies.